2023
DOI: 10.1021/acs.energyfuels.3c00377
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of Nanostructured Trimetallic Mn–V–Fe Selenides with Battery-Type Behavior for High-Performance Hybrid Supercapacitors

Abstract: The design and synthesis of innovative materials with a specific architecture are necessary to advance the supercapacitor industry. Recently, transition metal selenides have been identified as an auspicious type of material for energy storage devices due to their enormous electronic conductivity and high theoretical capacitance. Consequently, mono- and diselenides have been extensively investigated. Trimetallic selenides, however, are infrequently reported, and their charge storage mechanism is still not fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition, the contribution percentage for different scan rates is presented in Figure f. It can be observed that the diffusion-controlled contribution gradually decreases as the scan rate is increased, indicating the sluggish ion diffusion …”
Section: Resultsmentioning
confidence: 97%
“…In addition, the contribution percentage for different scan rates is presented in Figure f. It can be observed that the diffusion-controlled contribution gradually decreases as the scan rate is increased, indicating the sluggish ion diffusion …”
Section: Resultsmentioning
confidence: 97%
“…3(c)), which are ascribed to the metal-oxygen bond (M-O), and adsorbed oxygen containing species (such as H 2 O, O 2 , and CO 2 ), respectively. 2,61 However, the two wellresolved spin peaks in the high resolution XPS spectrum of S 2p (Fig. 3(d)) revealed the presence of oxidized sulfur species adsorbed on the surface in the form of sulfates and hydrogen sulfates through the peak located at 168.8 eV.…”
Section: Resultsmentioning
confidence: 99%
“…However, they still have lower energy density than rechargeable batteries. [1][2][3] The energy density of supercapacitors can be enhanced via two pathways: expanding the cell working voltage by using asymmetric supercapacitor devices and/or the proper choice of electrode materials. In this regard, nanostructured materials containing mixed metals and anions have been shown to outperform the conventional counterpart materials in terms of electrochemical performance and durability.…”
Section: Introductionmentioning
confidence: 99%
“…To keep up with the electronics revolution prevailing in the modern world, the ever increasing demand for energy, and exhaustion of fossil fuels, alternative and green energy storage platforms are essential. , In this regard, electrochemical supercapacitors with exceptional power density, lengthy lifespan, and environmental friendliness, are considered one of the most promising energy storage devices. , However, their practical application is hindered by their lower energy density than batteries. Both electrode and electrolyte materials are crucial for developing high-performance supercapacitors, according to the specific energy equation ( E = 1/2 CV 2 ), where E , C , and V are the specific energy density, the calculated capacitance, and the operating potential window, respectively. , In this context, considerable efforts have been devoted to developing electrode materials with superior specific capacitance.…”
Section: Introductionmentioning
confidence: 99%